Glucocorticoid-induced osteoporosis is prevented by dietary prune in female mice - Chargo, Nicholas J.; Neugebauer, Kerri; Guzior, Douglas V.; Quinn, Robert A.; Parameswaran, Narayanan; McCabe, Laura R. (Frontiers in Cell and Developmental Biology, 2024)
Glucocorticoid-induced osteoporosis (GIO) is a significant side effect of prolonged glucocorticoid (GC) treatment. Chronic GC treatment also leads to trabecular bone loss and gut microbiota dysbiosis in mice. The gut dysbiosis is mechanistically linked to GIO, which indicates that the microbiota can be targeted to prevent GIO. Prunes, a dried fruit and prebiotic, have emerged in the literature as an effective treatment for sex-steroid deficiency induced osteoporosis (primary osteoporosis). Prunes also significantly alter the composition of the gut microbiota in both rodent models and human studies. Therefore, we tested if dietary prune (DP) supplementation could prevent GC-induced bone loss and affect microbiota composition in an established model of GIO. Sixteen-week-old, skeletally mature, female C57BL/6J mice were treated with a subcutaneous 5 mg placebo or prednisolone pellet for eight weeks and fed an AIN-93M control diet or a diet modified to include 5, 15, or 25% (w/w) dried California prune powder. As expected, GC treated mice developed significant trabecular bone loss in the distal femur. More importantly, as little as 5% DP supplementation effectively prevented trabecular bone loss. Further, dose dependent increases in trabecular bone volume fraction were observed in GC + 15% and GC + 25% DP mice. Amazingly, in the placebo (non-GC treated) groups, 25% DP supplementation caused a ~3-fold increase in distal femur trabecular bone volume fraction; this sizable bone response has not been previously observed in healthy mice with gut targeted natural treatments. Along with the striking effect on bone health, GC treatment and 25% DP supplementation led to drastic shifts in gut microbiota composition and several specific changes are strongly associated with bone health. Taken together, these results are the first to demonstrate that DP supplementation effectively prevents the negative effects of prolonged GC therapy on trabecular bone health and strongly associates with shifts in the composition of the gut microbiota.